Assessment of Breast Cancer Management in Sub-Saharan Africa. (2021) - Vanderpuye, Verna; Dadzie, Mary-Ann; Huo, Dezheng; Olopade, Olufumilayo I.
Abstract : PURPOSE: To document progress and bottlenecks in breast cancer management in sub-Saharan Africa, subsequent to a 2013 pilot survey conducted through the African Organization for Research and Treatment in Cancer (AORTIC) network. METHODS: An anonymous survey of breast cancer management was conducted in 2018 among AORTIC members. Results concerning respondent specialty, access to tumor boards, treatment accessibility, diagnostic services, and factors influencing treatment outcomes were compared with the 2013 findings. RESULTS: Thirty-seven respondents from 30 facilities in 21 sub-Saharan Africa countries responded. The majority (92%) were clinical oncologists. Radiotherapy facilities were available in 70% of facilities. Seventy-eight percent of these had linear accelerators, and 42% had cobalt 60 machines. Eighty percent of facilities had multidisciplinary tumor boards. Immunohistochemistry was routinely performed in 74% of facilities, computed tomography scan in 90%, bone scan in 16%, and positron emission tomography scans in 5%. Anthracyclines, taxanes, tamoxifen, letrozole, anastrozole, and zoledronic acid were available in the majority; trastuzumab, fertility, and genetic counseling were available in 66%, 58%, and 16%, respectively. There were a 50% increase in oncologist respondents over 2013 and a > 50% increase in radiotherapy facilities, particularly linear accelerators. Availability of trastuzumab, aromatase inhibitors, and taxanes increased. Immunohistochemistry capacity remained the same, whereas facilities harvesting at least 10 axillary lymph nodes increased. Bone scan facilities decreased. Responses suggested improved diagnostic services, systemic therapies, and radiotherapy. Sociocultural and economic barriers, system delays, and advanced stage at presentation remain. CONCLUSION: Clinicians in sub-Saharan Africa have basic tools to improve breast cancer outcomes, recording positive strides in domains such as radiotherapy and systemic therapy. Socioeconomic and cultural barriers and system delays persist. Workforce expansion must be prioritized to improve quality of care to improve outcomes.